KEPENTINGAN SINGAPURA BERPARTISIPASI DALAM ReCAAP (REGIONAL COOPERATION AGREEMENT ON COMBATING PIRACY AND ARMED ROBBERY AGAINST SHIPS IN ASIA) - Saputra, Difran; Saeri, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Maritime security has become a critical issue in international relations, particularly in Southeast Asia, which is traversed by some of the world’s busiest shipping lanes. The Malacca Strait and the Singapore Strait, as global choke points, face threats of piracy and armed robbery that directly affect international trade. In response to these threats, Asian countries established ReCAAP as a regional maritime security cooperation mechanism. Unlike Indonesia and Malaysia, Singapore became the first country to ratify ReCAAP and has played an active role, including serving as the host of the Information Sharing Centre (ISC). This study aims to analyze the reasons and national interests behind Singapore’s participation in ReCAAP. The research employs a qualitative method through a literature study, using secondary data from official reports, policy documents, and academic publications. The analysis applies maritime security theory and the state level of analysis to explain Singapore’s foreign policy. The findings show that Singapore’s participation in ReCAAP is driven by its interest in safeguarding shipping lane security, protecting its national economy as a global trading hub, and strengthening its strategic position in the region. ReCAAP is considered effective because it emphasizes information sharing, capacity building, and inter-state coordination without direct military intervention. Therefore, Singapore’s involvement reflects a rational and proactive external security strategy in addressing non-traditional security threats in Southeast Asia. Keywords: Maritime Security, ReCAAP, National Interest, Singapore, the Malacca Strait and the Singapore Strait (SOMS)